Pengaruh Gaya Kepemimpinan, Motivasi, Disiplin Kerja Terhadap Kinerja Karyawan PT Adamas Manggala Perkasa Bandar Lampung - Astrid Aprica Isabella (Universitas Mitra Indonesia, 2020)
AbstractThis research aims to determine the influence of leadership style, motivation, work discipline on employee performance PT Adamas Manngala Perkasa, This research is a research with quantitative design with the number of samples of 77 samples. Methods of data collection using documentation and then analyzed using microsof word and excel 2010 and use multiple linear regression analysis processed using SPSS version 24.00 for windows.Based on the results of research in the know that the variable leadership style partially significant effect on employee performance, partial motivation variable has no effect on employee performance, and variable discipline partially significant effect on employee performance of PT AdamasManggala Perkasa. Anova Test Result (f test) shows that simultaneously Leadership style, motivation and discipline have a significant effect on employee performance of PTAdamasManggala Perkasa.